La pertinencia de los estudios coloniales para el nuevo milenio - Rolena Adorno (Instituto de Investigaciones en Ciencias Sociales y Humanidades, 2000)
Why devote oneself to colonial studies in Argentina? To respond to this question, I forward the hypothesis that current migrations and immigrations justify and foment interest in the colonial phenomenon; that is, that the paradigmatic colonial situation of the experience of moving from one place to another for economic reasons, be it or not under the force of arms, is reproduced today in many of its variants. These repetitions and transformations, in turn, stimulate the look back to to the sojourner subjects of long agoconquistadors, adventurers, tributary Indians or slaves. Furthermore, the proliferation of accounts that take as their object the colonial period reveals an interest much deeper than that of erudite speculation, popular history, or fiction; there exists a real passion for the colonial because it represents a paradigm from which to contemplate all the variants of colonialism (internal, external, neo- and post-) that exist today.